2009
DOI: 10.1002/eat.20712
|View full text |Cite
|
Sign up to set email alerts
|

Comparing definitions of purging disorder on point prevalence and associations with external validators

Abstract: Objective-We varied two defining features of Purging Disorder (PD): breadth of "purging" behaviors (purging only [narrow] vs. purging and nonpurging [broad]) and minimum behavioral frequency (once vs. twice per week) to examine their impact on syndrome validity.Method-Survey data from 1736 women and 755 men were used for analyses.Results-PD point prevalence was higher in women versus men, and prevalence was lowest for the narrow definition requiring purging twice per week. The narrow definition was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…19 A recent article compared varying definitions of Purging Disorder in terms of resulting point prevalence estimates and evidence of syndrome validity using external validators. 20 Although a narrow definition which required purging through the use of self-induced vomiting, laxative or diuretic abuse to influence weight or shape resulted in the lowest point prevalence (and smallest sample size for analyses), this narrowly defined group demonstrated statistically significant differences from a non-eating disorder group on psychosocial adjustment. Moreover, large effect sizes were found for comparisons of this narrowly defined group and non-eating disorder controls across several external validators.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…19 A recent article compared varying definitions of Purging Disorder in terms of resulting point prevalence estimates and evidence of syndrome validity using external validators. 20 Although a narrow definition which required purging through the use of self-induced vomiting, laxative or diuretic abuse to influence weight or shape resulted in the lowest point prevalence (and smallest sample size for analyses), this narrowly defined group demonstrated statistically significant differences from a non-eating disorder group on psychosocial adjustment. Moreover, large effect sizes were found for comparisons of this narrowly defined group and non-eating disorder controls across several external validators.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, both definitions of Purging Disorder resulted in groups that differed significantly from those without eating disorders on psychosocial adjustment, with nearly equivalent effect sizes. 20 Thus, reducing the minimum purging frequency to once per week did not reduce the homogeneity or clinical significance of the syndrome and allowed more individuals to move from the relatively heterogeneous and uninformative diagnosis of EDNOS to a homogeneous Purging Disorder group.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Our diagnoses needs to be considered tentative given that they were based on self-report and on a shorter time frame (28 days) than would be required for DSM-IV diagnoses. We note that selfreport based diagnoses are not uncommon in largescale studies 10,18,22,23 and that recent studies have used 28-day time frames. 18 Among women, aside from higher levels of restraint reported by those with BN, a variable not used for defining BN in our study, and higher mean BMI among those with BED, no significant differences were found when comparing those with BN versus BED.…”
Section: Discussionmentioning
confidence: 94%